Judicial Review of Mining Exploration-Exploitation Licenses-Permits and Revocations in Forest Areas - CESUR, İlknur; GÜLOĞLU, Yavuz (Kastamonu University, 2018)
Aim of study:
The aim of this study is to identify issues pertaining to the justifications of
the annulment decisions of the administrative judiciary in the cases of actions
for annulment brought against the revocations of mining licenses and permits
for mining activities granted by the administration due to reasons specified by
the legislation.

Area of study:
This study addresses licenses and permits granted for mining activities in
Turkey and judicial review of the revocations of these licenses and permits.

Material and Method:
The main material of the study is the current legislation on mining activities
and the judicial decisions for the cancellation of mining licenses / permits.
The method of study is to evaluate the materials together and to determine the
reasons for the cancellation and rejection decisions of the judiciary.

Main results:
Sanctions in the Mining Law should take into account future generations, stop
improper practices and ensure that mining activities are compatible with the
environment and human rights.

Research highlights:
Revocation of mining exploration-exploitation licenses in forest areas is an
issue that warrants further research and careful evaluation. Judicial decisions
play key role in filling the legal gaps in mining exploration and exploitation.
Keywords: 15. Life on land; 16. Peace & justice